THE ROLE OF CV. GRAHA PRATAMA FISH IN THE DEVELOPMENT AQUACULTURE BUSINESS OF CATFISH (Pangasius Sutchi) IN THE KOTO MESJID VILLAGE XIII KOTO KAMPAR SUB DISTRICT KAMPAR REGENCY OF RIAU PROVINCE - Parasian Sitorus; Kusai '; Ridar Hendri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted to find out the role of CV. Graha Pratama Fish in the development of the Aquaculture of catfish (Pangasius sutchi) in the Village of Koto Mesjid. The method used in this study was a survey method to thirteen respondents. Data was analysis descriptive. The results showed that CV. Graha Pratama Fish doing the role in opening up employment, assist in the acceleration of regional development, infrastructure improvement of Koto Mesjid Village. In the field of fisheries a role in providing seed catfish (Pangasius sutchi), fish feed suppliers, disseminators of information, motivator, skills coaches, and as a mediator for visitors in the Village of Koto Mesjid.Keywords: Role, Developmend, CV. Graha Pratama Fish